DK compact world atlas.. - DK Publishing, Inc. (London ; New York: Dorling Kindersley Publishing, 2005)
Features facts and statistics about the countries and regions of the world, and includes color maps, photographs, diagrams, and illustrations.
The political world -- The physical world -- Time zones -- The world atlas -- North & Central America -- Western Canada & Alaska -- Eastern Canada -- USA : the Northeast -- USA : the Southeast -- Bermuda -- USA : central states -- USA : the West -- Los Angeles & Hawaii -- USA : the Southwest -- Mexico -- Central America -- The Caribbean -- Jamaica, St. Lucia, & Barbados -- South America -- Northern South America -- Western South America -- Galapagos Islands -- Brazil -- Southern South America -- The Atlantic Ocean -- Africa -- Northwest Africa -- Northeast Africa -- West Africa -- Central Africa -- Sao Tome & Principe -- Southern Africa -- Europe -- The North Atlantic -- Scandinavia & Finland -- The low countries -- The British Isles -- London -- France, Andorra, & Monaco -- Paris, Andorra, & Monaco -- Spain & Portugal -- Azores & Gibraltar -- Germany & the Alpine states -- Liechtenstein -- Italy -- San Marino & Vatican City -- Central Europe -- Southeast Europe -- Bosnia & Herzegovina -- The Mediterranean -- Malta & Cyprus -- Bulgaria & Greece -- The Baltic states & Belarus -- Ukraine, Moldova, & Romania -- European Russia -- North & West Asia -- Russia & Kazakhstan -- Turkey & the Caucasus -- The Near East -- West Bank -- The MIddle East -- Central Asia -- South & East Asia -- Western China & Mongolia -- Eastern China & Korea -- Hong Kong (Xianggang) -- Japan -- T?oky?o & Nansei-Shot?o -- South India & Sri Lanka -- North India, Pakistan, & Bangladesh -- Mainland Southeast Asia -- Maritime Southeast Asia -- Singapore -- The Indian Ocean -- Australasia & Oceania -- The Southwest Pacific -- Western Australia -- Eastern Australia -- Sydney -- New Zealand -- The Pacific Ocean -- Antarctica -- The Arctic Ocean -- Index-Gazetteer -- Overseas territories & dependencies -- Countries factfile -- Geographical comparisons.
Relief shown by shading, gradient tints, and spot heights. Depths shown by gradient tints.
Includes index.
Keywords: Atlases